2012
DOI: 10.1108/09596111211197845
|View full text |Cite
|
Sign up to set email alerts
|

The effect of competitive strategies and organizational structure on hotel performance

Abstract: PurposeThe purpose of this paper is to investigate the influence of competitive strategies and organizational structure on hotel performance and to explore whether organizational structure has a moderating effect on the relationship between competitive strategies and hotel performance.Design/methodology/approachThis study employed a causal and descriptive research design to determine the cause‐and‐effect relationships among competitive strategies, organizational structure, and hotel performance based on previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 46 publications
(66 reference statements)
7
73
1
2
Order By: Relevance
“…The compilation period was about 3 months, with several requests made by telephone in order to solicit the answers. The final sample was composed of 110 agritourism businesses, which corresponded to a response rate of 11%; this compares favourably with rates reported in previous online surveys among tourism and hospitality operators [53].…”
Section: Methodological Designsupporting
confidence: 57%
“…The compilation period was about 3 months, with several requests made by telephone in order to solicit the answers. The final sample was composed of 110 agritourism businesses, which corresponded to a response rate of 11%; this compares favourably with rates reported in previous online surveys among tourism and hospitality operators [53].…”
Section: Methodological Designsupporting
confidence: 57%
“…IT should be connected with other non-IT company factors like strategy, clients, and services. Based on the analysis of different global proposals about how IT can improve hotel organizational performance (Chathoth, 2007;Law & Jogaratnam, 2005;Law et al, 2013;Leung & Law, 2005;Piccoli, 2008;Siguaw, Enz, & Namasivayam, 2000;Tavitiyaman, Qiu Zhang, & Qu, 2012), we posit that the general process involves acting upon the following organizational performance drivers: operational productivity, employee productivity, customer service, and commercialization (Fig. 1).…”
Section: Organizational Performance In Hotelsmentioning
confidence: 99%
“…On the other hand, the positive influence of human resources initiatives on hotels' performance was demonstrated by Sourouklis and Tsagdis (2013). Tavitiyaman et al, (2012) also suggested the human resources competitive strategies to influence directly hotel's behavioural performance, and the information technologies affect hotel's financial performance.…”
Section: Performancementioning
confidence: 99%
“…Other indicators that assess the financial performance of the hotel industry companies are the total revenues and the revenues per room (Chen, 2011;Chung and Kalnins, 2001;Xiao et al, 2012), the ratio between the net operating income and the operating expenses (Chen and Lin, 2012), the ROA (Return on Assets) (Tavitiyaman et al, 2012), the ROE (Return on Equity) and the stock return (Chen, 2011), the net profit (Tavitiyaman et al, 2012) and the net profit margin (Jae and Jang, 2007).…”
Section: Performancementioning
confidence: 99%
See 1 more Smart Citation